Medical Students’ Perception on the Ideal Lecturer Attributes in Problem-Based Learning on the Onion Model Theory - Erlangga, M. Ramses; Meidianawaty, Vivi; Permatasari, Tissa Octavira (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: The success of Problem-Based Learning (PBL) is closely related to an effective discussion process. A good PBL will affect the success of the learning process. In addition, an effective teaching process from lecturers to students is very influential in producing a qualified doctor. Korthagen's Onion Model is a theory that emphasizes layered aspects in communication and can provide an in-depth view of the relationship between lecturers and students in the context of learning, such as PBL. Aims: To identify what is the ideal lecturer attributes in Problem Based Learning based on the onion model theory according to medical faculty students. Methods: This study uses a descriptive method. Respondents were selected using stratified random sampling techniques, resulting in 98 respondents. This study uses primary data with univariate analysis. Results: From the 98 analyzed samples, it was found that level 1 students gave the highest average score on the identity aspect, with the following average scores: Level 1 (14.4167), Level 2 (13.1111), Level 3 (12, 6667), and Level 4 (12.7826). The behavioral aspect also showed similar results, with the highest score at Level 1 (14.0417) followed by Level 2 (13.5926), Level 3 (13.2083), and Level 4 (13.1739). Conclusion: Most students of the Faculty of Medicine, Universitas Swadaya Gunung Jati, have a good perception of the attributes of ideal lecturers in Problem-Based Learning based on the Onion Model Theory.